2022
DOI: 10.3390/su14052936
|View full text |Cite
|
Sign up to set email alerts
|

Should I Stay or Can I Go? Accessible Tourism and Mountain Huts in Gran Paradiso National Park

Abstract: Within the tourism sector, sustainability has been studied widely at different levels and with different lenses. In the last few years, many research activities have been carried out to assess the social dimension of tourism. Under this perspective, scholars have focused on the accessibility of the tourism and hospitality sectors. This study represents the first-ever attempt to assess how tourists’ physical handicaps or special needs are considered in a very specific kind of accommodation facility: the mountai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Making tourism more accessible also means eliminating barriers for people with special food needs (Cañulaf & Rodríguez, 2015). Beltramo, Duglio & Cappelletti (2022) analysed accessibility in mountain shelters in Gran Paradiso National Park in Italy and found that all shelter managers had adapted their facilities to accommodate guests with special dietary requirements who now constitute a significant part of their customers, thus demonstrating their ability to change operational processes, habits and behaviours in response to new market requirements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Making tourism more accessible also means eliminating barriers for people with special food needs (Cañulaf & Rodríguez, 2015). Beltramo, Duglio & Cappelletti (2022) analysed accessibility in mountain shelters in Gran Paradiso National Park in Italy and found that all shelter managers had adapted their facilities to accommodate guests with special dietary requirements who now constitute a significant part of their customers, thus demonstrating their ability to change operational processes, habits and behaviours in response to new market requirements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The scholarly literature on accessibility in tourist attractions examines various facets of the issue. Some researchers have concentrated on highlighting the challenges that persons with disabilities have when traveling, both when going to tourist attractions and other places (Beltramo et al, 2022;Hennig et al, 2015;McIntosh, 2020). In particular, accessibility how important it is for persons with disabilities to choose buildings that are accessible and, most importantly, accommodate their needs (Darcy, 2006).…”
Section: Accessibilitymentioning
confidence: 99%